ASPECTS REGARDING THE METHODOLOGY AND METHODS OF LEARNING VOLLEYBALL IN THE BEGINNER GROUPS - UNGUREAN Bogdan Constantin (Editura Universitatii Transilvania din Brasov, 2020)
Purpose: Taking into account that the finality of the instructiveeducative process at the level of the beginners' group is to accomplish as much as possible the model of player and the team's game model and on this basis, promotion to the teams of advanced I, my goal in this paper was to help enrich the theoretical, practical-methodical of the volleyball game at the level of beginners, based on the most recent views provided by the scientific literature. The research was carried out for a year with a group of 25 children (girls) aged 11±1. The students were monitored within the Physical Education classes and, by their somatic skills, they were selected in the beginners' group. Following the study, it has been concluded that positive results were obtained at the final evaluations, which confirms once again the formative valences of the training activity in the attaining of the objectives proposed.